EVALUATING COMPETITIVENESS OF AIPORTS - AIRPORT COMPETITIVENESS INDEX - Grancay, Martin (Doprava a spoje, 2009)
The paper introduces a concept of airport competitiveness index. The index consists of numerous indicators grouped into four categories: market potential, infrastructure, charges and recent traffic results. Another important factor we take into account is safety. We find that from the selected sample the most competitive airports are Singapore Changi and NY Kennedy.